Determinan Pembiayaan Murabahah Pada Unit Usaha Syariah: Model Regresi Panel - Ahmad Wahyudi (Faculty of Economic and Business, 2016)
Determinant of Murabahah Financing in Islamic Business Unit: Panel Regression ModelFinancing is one main activity in Islamic banking operations. The aim of this research is to determine the factors that influence the financing in Islamic business unit. This research is using panel regression as a tool of analysis. The sample that used in this object is five Islamic business unit, such as Bank of BTN, Bank of Permata, Bank of CIMB Niaga, Bank of DKI, and Bank of West Kalimantan. The result shows that only deposit funds that have an influence to murabahah financing in Islamic business unit, otherwise the operational efficiency ratio (BOPO) doesn't have an impact on financing.DOI: 10.15408/ess.v6i2.3776